Nonlinear control - Khalil, Hassan K. 1950- (Pearson Education Limited, 2015)
For a first course on nonlinear control that can be taught in one semester This book emerges from the award-winning book, Nonlinear Systems, but has a distinctly different mission and organization. While Nonlinear Systems was intended as a reference and a text on nonlinear system analysis and its application to control, this streamlined book is intended as a text for a first course on nonlinear control. In Nonlinear Control, author Hassan K. Khalil employs a writing style that is intended to make the book accessible to a wider audience without compromising the rigor of the presentation. Teaching and Learning Experience This program will provide a better teaching and learning experience-for you and your students. It will help: *Provide an Accessible Approach to Nonlinear Control: This streamlined book is intended as a text for a first course on nonlinear control that can be taught in one semester. *Support Learning: Over 250 end-of-chapter exercises give students plenty of opportunities to put theory into action